1996
DOI: 10.1037/0022-0663.88.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Student conceptions of learning and their use of self-regulated learning strategies: A cross-cultural comparison.

Abstract: This study examines differences between Australian and Japanese secondary school students' conceptions of learning and their use of self-regulated learning strategies. Australian students have a narrow, school-based view of learning. The Japanese students view learning from a much broader perspective. For them, learning is not only related to what happens at school, it is also seen as a lifelong, experiential process leading to personal fulfillment. However, in spite of these differences in learning conceptual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
162
2
28

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(208 citation statements)
references
References 53 publications
11
162
2
28
Order By: Relevance
“…They found that qualitative conceptions (such as 'learning is concerned with understanding and meaning by relating or connecting new material to prior knowledge') were particularly linked with deep processing. Furthermore, more advanced conceptions in which learning is seen as understanding instead of memorising, are found to be associated with a more frequent use of self-regulated learning strategies (Purdie et al 1996). Ferla et al 2008 tested a structural model in which conceptions of learning were related with regulation and processing strategies.…”
Section: Relationships Between Conceptions Of Learning and Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that qualitative conceptions (such as 'learning is concerned with understanding and meaning by relating or connecting new material to prior knowledge') were particularly linked with deep processing. Furthermore, more advanced conceptions in which learning is seen as understanding instead of memorising, are found to be associated with a more frequent use of self-regulated learning strategies (Purdie et al 1996). Ferla et al 2008 tested a structural model in which conceptions of learning were related with regulation and processing strategies.…”
Section: Relationships Between Conceptions Of Learning and Regulationmentioning
confidence: 99%
“…It is hypothesized based on previous research on conceptions of learning (e.g., Ferla et al 2008;Purdie et al 1996) that relationships exist between conceptions of constructivist learning and regulation and processing strategies, since previous research on conceptions of constructivist learning demonstrated relationships with learning activities such as self-study time and study preparation and participation (Loyens et al 2007b). Furthermore, it is expected that conceptions of self-regulated learning show significant relationships with actual self-regulated learning activities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(BOULTON-LEWIS et al, 2004;CANO;CARDELLE-ELAWAR, 2004;PURDIE;HATTIE;DOUGLAS, 1996). Estos resultados han llevado a proponer que las concepciones de aprendizaje estarían constituidas por algunos elementos propios de una situación educativa, los que le darían un cierto carácter universal, no obstante los matices y énfasis que pueden ser aportados desde cada contexto cultural.…”
Section: Terrazas W Análisis Lexicométrico Aplicado Al Estudio De Lunclassified
“…Asimismo, categorías complementarias han surgido de otras investigaciones, tales como procesamiento de la información, aprendizaje experiencial (TYNJÄLÄ, 1997) y desarrollo personal, entre otras. (PURDIE;HATTIE;DOUGLAS, 1996).…”
Section: Terrazas W Análisis Lexicométrico Aplicado Al Estudio De Lunclassified